TYPES AND PLACE AND IMPORTANCE OF THE NATIONAL BIRD IN THE SYSTEM OF PHYSICAL TRAINING: TYPES AND PLACE AND IMPORTANCE OF THE NATIONAL BIRD IN THE SYSTEM OF PHYSICAL TRAINING - Kholdorova, Maftuna (Физическое воспитание, спорт и здоровье, 2022)
This article discusses the role of Uzbek national wrestling in the world arena, stages of development, development of society, the younger generation that can rationally solve future social problems, as well as the importance of Uzbek national wrestling in physical and intellectual development.